From assets to profits : competing for IP value & return - Berman, Bruce M. (Hoboken, N.J. : John Wiley & Sons, 2009)
Industry-leading managers and investors show how to incorporate the best intellectual property rights into the latest business models. The information age is opening new doors. Intellectual property rights such as patents, copyrights, and trademarks are among companies' most valuable assets. Today, managers, executives, and investors must understand the fundamentals of IP to be in a position to make informed business decisions. Edited by industry expert Bruce Berman and with contributions from the top names in IP management, investment, and consulting, From Assets to Profits provides a detailed look at how intellectual property assets work and what professionals need to know about them to succeed in today's competitive business environment. From Assets to Profits, explores how recent developments are forcing businesses to reexamine their approach to innovation and performance, and explains how to recognize IP assets and deploy them for the best return.
Includes bibliographical references and index.
Keywords: Intellectual capital -- Valuation; Intellectual property; Technological innovations -- Economic aspects; Patent Licenses